2014
DOI: 10.1538/expanim.13-0104
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Diversity in Rat Model Induced by Rhubarb

Abstract: Rhubarb is often used to establish chronic diarrhea and spleen (Pi)-deficiency syndrome animal models in China. In this study, we utilized the enterobacterial repetitive intergenic consensuspolymerase chain reaction (ERIC-PCR) method to detect changes in bacterial diversity in feces and the bowel mucosa associated with this model. Total microbial genomic DNA from the small bowel (duodenum, jejunum, and ileum), large bowel (proximal colon, distal colon, and rectum), cecum, and feces of normal and rhubarb-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…Interestingly, rhubarb, the major natural source of rhein, was traditionally used as a purgative in China, and was often used to establish chronic diarrhoea animal models ( Qin et al, 2011 ). Although recent studies suggested that rhubarb extract induced gut microbial diversity in rats, and helped to prevent obesity in mice on a chronic high-fat diet ( Peng et al, 2014 ; Wang et al, 2016 ), our results suggest that rhein may act in the intestinal lumen and be one of the effective constituents functioning in the intestinal lumen.…”
Section: Resultscontrasting
confidence: 73%
“…Interestingly, rhubarb, the major natural source of rhein, was traditionally used as a purgative in China, and was often used to establish chronic diarrhoea animal models ( Qin et al, 2011 ). Although recent studies suggested that rhubarb extract induced gut microbial diversity in rats, and helped to prevent obesity in mice on a chronic high-fat diet ( Peng et al, 2014 ; Wang et al, 2016 ), our results suggest that rhein may act in the intestinal lumen and be one of the effective constituents functioning in the intestinal lumen.…”
Section: Resultscontrasting
confidence: 73%
“…For example, Wang et al ( 2016 ) used an anti-inflammatory agent to show that chronic rhein (the main ingredient of rhubarb plant with anti-inflammatory properties) treatment prevented HFD-induced recognition memory impairment. The rhubarb-exposed rats also had an increased bacterial diversity in the ileum, which could also contribute or reflect the beneficial effects of the treatment (Peng et al, 2014 ). Wang et al ( 2017 ) demonstrated that teasaponin, an active component of tea with anti-inflammatory effects, limit unfavorable gut microbiota alterations, reduced body weight, improved glucose tolerance and prevent recognition memory impairment in HFD-fed mice; it also improved neuroinflammation, gliosis and BDNF deficits in hippocampus.…”
Section: Effects Of Obesity On Cognitive Functions and Moodmentioning
confidence: 99%
“…Therefore, more experimental research has focused on the relationship between disease and gastrointestinal microflora. Besides, research has shown that some traditional Chinese drugs exert their effects on disease by regulating the equilibrium of intestinal microflora[ 10 , 11 ]. Many molecular biology techniques have been used to illustrate gut microbial diversity, including denaturing/temperature gradient gel electrophoresis, terminal restriction fragment length polymorphism, and high-throughput sequencing[ 12 ].…”
Section: Introductionmentioning
confidence: 99%